2017
DOI: 10.1007/s11356-017-9180-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of palm oil mill sludge biochar preparation for sulfur dioxide removal

Abstract: In this study, palm oil mill sludge was used as a precursor to prepare biochar using conventional pyrolysis. Palm oil mill sludge biochar (POSB) was prepared at different preparation variables, i.e., heating temperature (300-800 °C), heating rate (10-20 °C/min) and holding time (60-120 min). The prepared biochars were tested for sulfur dioxide (SO) adsorption in a fixed bed reactor using 300 ppm of SO gas at 300 ml/min (with N gas as balance). Response surface central composite experimental design was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…types of biomass, process temperature) during the pyrolysis process. 8,9,15,16 It was also reported that the biochar surface area provides adsorption properties that can be applied in numerous applications, acting as soil amendment for planting, [17][18][19] carbon dioxide (CO 2 ) and sulphur dioxide (SO 2 ) gas adsorbent, 20,21 removal of heavy metal in wastewater, 22 industrial effluent treatment, 23 precursor of activated carbon [24][25][26] and production of supercapacitor electrodes. 27 In this study, SMS was converted into biochar using microwave vacuum pyrolysis, then the biochar was used as a new ingredient added to mushroom substrate to cultivate Pleurotus species mushroom (Oyster mushroom).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…types of biomass, process temperature) during the pyrolysis process. 8,9,15,16 It was also reported that the biochar surface area provides adsorption properties that can be applied in numerous applications, acting as soil amendment for planting, [17][18][19] carbon dioxide (CO 2 ) and sulphur dioxide (SO 2 ) gas adsorbent, 20,21 removal of heavy metal in wastewater, 22 industrial effluent treatment, 23 precursor of activated carbon [24][25][26] and production of supercapacitor electrodes. 27 In this study, SMS was converted into biochar using microwave vacuum pyrolysis, then the biochar was used as a new ingredient added to mushroom substrate to cultivate Pleurotus species mushroom (Oyster mushroom).…”
Section: Introductionmentioning
confidence: 99%
“…types of biomass, process temperature) during the pyrolysis process . It was also reported that the biochar surface area provides adsorption properties that can be applied in numerous applications, acting as soil amendment for planting, carbon dioxide (CO 2 ) and sulphur dioxide (SO 2 ) gas adsorbent, removal of heavy metal in wastewater, industrial effluent treatment, precursor of activated carbon and production of supercapacitor electrodes …”
Section: Introductionmentioning
confidence: 99%
“…In the third stage, there is a stabilization of the mass loss rate, which also indicates a decrease in the conversion process. Soon after, on the DTG curve, it was possible to observe the presence of two peaks: the first started between 200 and 235 ºC, with a 12% of weight loss of hemicellulose degradation and the second, between 235 and 330 ºC related to the cellulose degradation [37,38]. Lignin is a macromolecule that is difficult to decompose and presents showing a prominent degradation from 330 ºC until the stabilization at approximately 500 ºC.…”
Section: Raw Materials Characterizationmentioning
confidence: 99%
“…SO 2 and H 2 S analyzers recorded the gas concentrations every second. The adsorption capacity was calculated from the following equation [58] using the breakthrough curve generated during the experiment:…”
Section: Adsorption Testsmentioning
confidence: 99%